Calcium regulation by thermo- and osmosensing transient receptor potential vanilloid channels (TRPVs) in human conjunctival epithelial cells - Mergler, Stefan; Garreis, Fabian; Sahlmueller, Monika; Lyras, Ekaterini-Maria; Reinach, Peter S.; Dwarakanath, Abhilash; Paulsen, Friedrich; Pleyer, Uwe (Histochemistry and Cell Biology, 2012)
Transient receptor potential vanilloid (TRPV) channels respond to polymodal stresses to induce pain, inflammation and tissue fibrosis. In this study, we probed for their functional expression in human conjunctival epithelial (HCjE) cells and ex vivo human conjunctivas. Notably, patients suffering from dry eye syndrome experience the same type of symptomology induced by TRPV channel activation in other ocular tissues. TRPV gene and protein expression were determined by RT-PCR and immunohistochemistry in HCjE cells and human conjunctivas (body donors). The planar patch-clamp technique was used to record nonselective cation channel currents. Ca 2+ transients were monitored in fura-2 loaded cells. Cultivated HCjE cells and human conjunctiva express TRPV1, TRPV2, and TRPV4 mRNA. TRPV1 and TRPV4 localization was identified in human conjunctiva. Whereas the TRPV1 agonist capsaicin (CAP) (5-20 μM) -induced Ca 2+ transients were blocked by capsazepine (CPZ) (10 μM), the TRPV4 activator 4α-PDD (10 μM) -induced Ca 2+ increases were reduced by ruthenium-red (RuR) (20 μM). Different heating (<40°C or>43°C) led to Ca 2+ increases, which were also reduced by RuR. Hypotonic challenges of either 25 or 50% induced Ca 2+ transients and nonselective cation channel currents. In conclusion, conjunctiva express TRPV1, TRPV2, and TRPV4 channels which may provide novel drug targets for dry eye therapeutics. Their usage may have fewer side effects than those currently encountered with less selective drugs. © Springer-Verlag 2012.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Dry eye; Human conjunctiva; Intracellular Ca; Planar patch-clamp; TRPV channels